Identifikasi Hambatan Guru Pada Pelaksanaan Pembelajaran Tematik Di SD (Jurnal Keguruan dan Ilmu Pendidikan, 2022)
This study aims to odentify obstacles to the implementation of thematic learning at SD. This research uses a qualitative approach with a descriptive type of research. Data were collected through interviews, observation and documentation. The research location is in Malango' Tagari 1 Christian Elementary School which has implemented the 2013 Curriculum. The research subjects are low grade teachers (class I, II, III) who teach at Malango' Tagari 1 Christian Elementary School. The object of this research is the teacher's activity in implementing thematic learning. The data collected will be analyzed using the flow developed by Mills & Huberman, namely data collection as the first step, then data reduction, data display, and conclusion are drawn. The result showed that the obstacles to the implementation of thematic learning at SD Kristen Malango Tagari 1 were (1) the limited understanding of teachers about the concept of development of elementary school-aged children and their characteristics because they were only obtained during educational lectures and had an impact on teachers being less than optimal in carrying out thematic learning according to children’s development, (2) the limited jnowledge of teachers regarding the implementation of thematic learning, so that it has an impact on the absence of some thematic learning characteristics, (3) the factors that hinder the implementation of thematic learning are. a) undisciplined teachers. Time in terms of completing teacher administrative tasks, b) teacher do not really understand about the development of thematic learning in lesson plans, c) teachers have difficulty integrating themes into existing schedules, d) teachetrs have difficulty mananing the learning process of low grade students due to lack of understanding in child development elementary school age, e) the teachers does not focus on the material being taught.